The initiation of pull‐apart basins and transform continental margins: results from numerical experiments of kinematic partitioning in divergent settings. (20th January 2016) - Basile, Christophe; Braun, Jean
Abstract: We present a set of numerical models to investigate how transform faults initiate in pull‐apart basins or transform continental margins. The model represents an elastic plate with three aligned weak spots. Applying strain on the edge of the model firstly propagates extensional cracks from the pre‐existing damaged spots. The subsequent evolution depends on the angle (obliquity) between the applied strain and the alignment of the damaged spots. For obliquity <50°, transform faults form to connect en‐échelon divergent cracks; for obliquity >60°, transtensional transfer zones connect the divergent cracks and no transform fault forms. These experiments suggest that pull‐apart basins do not form as previously assumed by connection of overlapping transform faults, but that transform faults form as connections of extensional areas.